2012
DOI: 10.1186/cc11410
|View full text |Cite
|
Sign up to set email alerts
|

Survival and neurologic outcome after traumatic out-of-hospital cardiopulmonary arrest in a pediatric and adult population: a systematic review

Abstract: IntroductionThis systematic review is focused on the in-hospital mortality and neurological outcome of survivors after prehospital resuscitation following trauma. Data were analyzed for adults/pediatric patients and for blunt/penetrating trauma.MethodsA systematic review was performed using the data available in Ovid Medline. 476 articles from 1/1964 - 5/2011 were identified by two independent investigators and 47 studies fulfilled the requirements (admission to hospital after prehospital resuscitation followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
3
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 32 publications
5
72
3
11
Order By: Relevance
“…The overall survival rate in our study population was 3.4% (11/328), which was similar to most previous studies of 0%–22% (mean, 4.4%) 2. Prior studies have shown that EMS personnel were able to accurately determine TCPA in the field and that violation of the TOR guidelines for TCPA would result in unnecessary resuscitation and hospital transport, potentially leaving the victim in a neurologically devastated state 13 14…”
Section: Discussionsupporting
confidence: 86%
“…The overall survival rate in our study population was 3.4% (11/328), which was similar to most previous studies of 0%–22% (mean, 4.4%) 2. Prior studies have shown that EMS personnel were able to accurately determine TCPA in the field and that violation of the TOR guidelines for TCPA would result in unnecessary resuscitation and hospital transport, potentially leaving the victim in a neurologically devastated state 13 14…”
Section: Discussionsupporting
confidence: 86%
“…Survival from cases of traumatic out-of-hospital cardiac arrest (OHCA) is generally reported to be low, with a recent systematic review reporting an overall survival of 3.3% 1. Despite this, there has been an emerging interest in traumatic OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates from traumatic arrest have been poor, with approximately 2% of patients surviving to hospital discharge(1). However, more contemporary studies from diverse settings and locations including military experience(2), Australia(3), England(4), the United States(5), Spain(6), and a recent systematic review(7) report survival rates between 5-8%.…”
Section: Introductionmentioning
confidence: 99%